Factors associated with women’s interest in contraceptive implant use at a community health center - Lasria Yolivia Aruan; Sri Rezeki; Gusti Artha Nainggolan; Rasmi Manullang; Plora Novita Febrina Sinaga; Nurbaiti Nurbaiti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Despite being one of the most effective long-acting reversible contraceptive methods, the utilization of contraceptive implants remains low in Indonesia. Limited knowledge, sociodemographic characteristics, and inadequate husband support are considered important barriers to implant acceptance. Purpose: To identify factors associated with the low interest of women in using contraceptive implants. Method: An analytical correlational study with a cross-sectional design was conducted among 40 women of reproductive age who were family planning acceptors. A total sampling technique was employed. Primary data were collected using structured questionnaires, while secondary data were obtained from health center records. Data were analyzed using descriptive statistics and Fisher's Exact Test with a significance level of p<0.05. Results: Among the 40 respondents, the majority were aged 20–35 years (52.5%), had a secondary level of education (55.0%), demonstrated poor knowledge of contraceptive implants (45.0%), and reported a lack of husband's support (65.0%). Only 37.5% of the respondents expressed interest in using contraceptive implants. Fisher's exact test revealed that knowledge (p<0.001), age (p=0.005), educational level (p<0.001), and husband's support (p<0.001) were all significantly associated with respondents interest in using contraceptive implants. Respondents with better knowledge, higher educational attainment, older reproductive age, and supportive husbands were more likely to express interest in using contraceptive implants. Conclusions: Knowledge, age, education, and husband support are significant determinants of women's interest in contraceptive implant use. Strengthening family planning education and involving husbands in counseling may improve acceptance of implant contraception.